Kejadian Hiperbilirubinemia Ditinjau dari Berat Badan Lahir - yeviza Puspitasari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
Hyperbilirubinemia is one of the clinical phenomena most often found in neonates occurring in the first week of life, which is also one of the factors causing infant death is influenced by the immature liver function of the baby to process erythrocytes (red blood cells), resulting in the accumulation of bilirubin. The purpose of this study was to determine the relationship of birth weight of infants with the incidence of hyperbilirubinemia in RSUD dr. Ibnu Soetowo Baturaja Ogan Komering Ulu Regency in 2019. This study uses analytic methods with a cross-sectional approach. The study population was all infants aged 0-7 days in the neonatal room at RSUD dr. Ibnu Soetowo Baturaja Ogan Komering Ulu Regency in 2019, with a random sampling. Data analysis uses univariate analysis and bivariate analysis using distribution tables and Chi-Square statistical tests, with a 95% confidence level. In the univariate analysis, of 203 respondents found 26.5% had hyperbilirubinemia and those without hyperbilirubinemia 72.5%, 24.6% of infants with LBW and non-LBW infants 75.4%. Bivariate analysis showed that there was an LBW relationship with the incidence of hyperbilirubinemia (p-value 0,000).